Feasibility of paper microzone plates for greener determination of the alcoholic content of beverages by thermal infrared enthalpimetry. Issue 39 (17th September 2019) - Voss, Mônica; Schlessner, Sandra Kunde; Ferreira, Daniele; Oliveira, Alessandra Stangherlin; Deprá, Mariany Costa; Jacob-Lopes, Eduardo; Barin, Juliano Smanioto
Abstract : Direct determination of ethanol in paper devices based on the temperature change of the mixture with water (heat of dilution). Abstract : A new method is proposed in this work, combining paper devices and thermal infrared enthalpimetry (TIE) for simple, green and high-throughput determination of the alcoholic content of distilled beverages (cachaça, gin and vodka). The heat of dilution between water and ethanol was explored and the temperature changes were measured using an infrared camera. The results obtained with TIE in combination with paper microzone plates (TIE-P) were compared with those of the official method AOAC 942.06 and they presented an agreement of 98.8–101.4% for cachaça, 99.2–99.5% for vodka and 99.4 to 101.4% for gin samples. A high sample throughput was achieved, reaching 480 samples per h. The greenness of the proposed method TIE-P, TIE in polystyrene microplates (TIE-PS) and the AOAC method was evaluated using the green analytical procedure index (GAPI) and life cycle analysis (LCA). Using TIE-P, it was possible to reduce energy consumption by three orders of magnitude compared to the AOAC method. In addition, a significant reduction in the analysis time was observed: from 75 min (for the AOAC method) to 0.125 min per sample. The global warming potentials of the TIE-P, TIE-PS and AOAC methods were 1.9 × 10 −5, 1.55 × 10 −4 and 7.22 kg CO2eq, respectively. The use of the paper device as a reactor for TIE provided a 24 and 2000 times reduction in the water footprint in relation to the use of polystyrene microplates for TIE and the AOAC method, respectively. Therefore, the proposed method could be considered greener and in accordance with the principles of green chemistry.